The Life Cycle Model of Cyber-economics - Nowduri, Srinivas (Archives of Business Research, 2020)
The exponential increase in modern technological advancements within the business world, is impacting every national economy from different directions/perspectives. This research work focuses on main issues behind cyber economics along with cyber-economic values; based on cyber events and their associated financial damages. It also made a comparative study between cyber and financial metrics, based on a professional look at cybersecurity in modern digital firms. Then it emphasizes on the role of applied and behavioral economics, in digital forms. Finally propose a model for cyber economic growth vital for modern digital firms